Changing behaviour: an essential component of tackling health inequalities. (10th February 2021) - Marteau, Theresa M; Rutter, Harry; Marmot, Michael
Abstract : Theresa Marteau and colleagues argue that behavioural and social causes of poor health must be tackled in parallel to reduce inequalities